2016
DOI: 10.1002/2014ja020799
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric data assimilation and forecasting during storms

Abstract: Ionospheric storms can have important effects on radio communications and navigation systems.Storm time ionospheric predictions have the potential to form part of effective mitigation strategies to these problems. Ionospheric storms are caused by strong forcing from the solar wind. Electron density enhancements are driven by penetration electric fields, as well as by thermosphere-ionosphere behavior including Traveling Atmospheric Disturbances and Traveling Ionospheric Disturbances and changes to the neutral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
79
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 56 publications
(69 reference statements)
2
79
0
Order By: Relevance
“…Chartier et al . [] assimilated the ground‐based TEC observations into a coupled thermosphere‐ionosphere model during a major storm of Kp 7–8 and evaluated their model capabilities/performances for storm time short‐term forecasting. Using synthetically generated observations, Chartier et al .…”
Section: Introductionmentioning
confidence: 99%
“…Chartier et al . [] assimilated the ground‐based TEC observations into a coupled thermosphere‐ionosphere model during a major storm of Kp 7–8 and evaluated their model capabilities/performances for storm time short‐term forecasting. Using synthetically generated observations, Chartier et al .…”
Section: Introductionmentioning
confidence: 99%
“…Hsu et al (2018) did several observing system simulation experiments (OSSEs) based on the Ensemble Square Root Filter (EnSRF) for COSMIC-2 observations and concluded that the assimilation of slant TEC data from COSMIC-2 can considerably improve the global ionospheric specification and prediction. However, in these above studies, the authors usually applied the commonly used software packages to implement EnKF/EnSRF, including the Gridpoint Statistical Interpolation (Hsu et al, 2018;Wu et al, 2002) and the Data Assimilation Research Testbed (Anderson et al, 2009;Chartier et al, 2016;Chen et al, 2017;Lee et al, 2012;Matsuo et al, 2013;Pedatella et al, 2018), which rely on large-scale parallel high-performance computing systems. However, in these above studies, the authors usually applied the commonly used software packages to implement EnKF/EnSRF, including the Gridpoint Statistical Interpolation (Hsu et al, 2018;Wu et al, 2002) and the Data Assimilation Research Testbed (Anderson et al, 2009;Chartier et al, 2016;Chen et al, 2017;Lee et al, 2012;Matsuo et al, 2013;Pedatella et al, 2018), which rely on large-scale parallel high-performance computing systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of previous studies were conducted on supercomputers, such as NCAR Yellowstone (Chartier et al, 2016;Hsu et al, 2014;Lee et al, 2012;Matsuo et al, 2013) or Cheyenne supercomputer (Pedatella et al, 2018). However, the majority of previous studies were conducted on supercomputers, such as NCAR Yellowstone (Chartier et al, 2016;Hsu et al, 2014;Lee et al, 2012;Matsuo et al, 2013) or Cheyenne supercomputer (Pedatella et al, 2018).…”
mentioning
confidence: 99%
“…This approach has been applied to assimilate thermospheric/ionospheric observations into a three-dimensional global thermosphereionosphere coupled model, National Center for Atmospheric Research Thermosphere-Ionosphere-Electrodynamics General Circulation Model (NCAR TIE-GCM) (Matsuo and Araujo-Pradere 2011;Lee et al 2012Lee et al , 2013Chartier et al 2013Chartier et al , 2016Hsu et al 2014;Chen et al 2016). Chen et al (2016) successfully constructed a module capable of assimilating ground-based GPS total electron content (TEC) observations to this ionospheric data assimilation system.…”
Section: Introductionmentioning
confidence: 99%